ELECTRONIC STRUCTURE AND QUANTUM-CHEMICAL ACCOUNT OF FURFUROLIDENUREA (Scientific journal of the Fergana State University, 2023)
Today, important research is being conducted in the field of accurately describing the properties of high-molecular compounds and the chemical reactions involved in them with high theoretical accuracy.This paper presents the results of the reactivity of furfural and urea molecules required to obtain furfuralidenurea calculated using a modern Gaussian98 computer program. The electronic structure of the furfuralidenurea molecule, optimized geometric parameters, atomic charges were calculated with high accuracy. Theoretically necessary results were obtained on the reactivity of the compound.